Methods of training as the system development of the competence of personnel (Вестник КазНУ. Серия Экономическая, 2016)
The man recognized as the most valuable resource of the organization. It is connected also with the fact that the personnel – the adaptive kind of resources. Because of this adaptability organization is able to change quickly in response to the unexpected demands of the external environment, to maintain control in conditions of instability of the parameters of time constraints and lack of other resources.Thus, the personnel have become a major competitive advantage and resource companies. And the training is the same investment of capital, as well as investments in fixed assets. In practice the training begins because the leaders have decided that it is necessary. A professional approach to the organization of training considering it as part of an overall personnel management system. Education directly related to the analysis and design work, the selection of personnel, organization of the system of compentence, evaluation of staff performance. This article focuses on training, namely the choice of teaching methods, evaluation of the effectiveness of training programs.
Keywords: training; teaching methods; motivation; learning process; advantages of training.